Near-Infrared Spectroscopy Allows for Monitoring of Bone Fracture Healing via Changes in Oxygenation - Cedric Nowicki; Bergita Ganse (Journal of Functional Biomaterials)
Bone fractures are associated with hypoxia, but no longitudinal studies of perfusion measurements in human patients have been reported despite the clinical and research potential. In this longitudinal observational cohort study, the near-infrared spectroscopy (NIRS) device PortaMon was used to assess oxy-(O2Hb), deoxy-(HHb) and total (tHb) haemoglobin, as well as the differences between O2Hb and HHb (HbDiff) and the tissue saturation index (TSI) at three different depths in the fracture gap. Linear mixed effect models were fitted to analyse time effects. One-way ANOVAs were conducted to compare groups. The time points corresponding to minima were calculated via linear regression. In this study, 11 patients with tibial shaft fractures underwent longitudinal measurements. Additionally, 9 patients with diagnosed tibial shaft nonunion and 23 age-matched controls were measured once. In the longitudinal group, all fractures healed, and decreases in O2Hb and HbDiff (all p < 0.05) were observed, with minima occurring 19–21 days after fracture. O2Hb values in nonunion patients did not differ from the minima in longitudinally measured union patients, whereas differences in HHb and tHb were significant (all p < 0.05). Previously, the onset of hypoxia has been assumed to be much faster. The characteristic trajectories of the NIRS parameters O2Hb and HbDiff can be used to fulfil the need for a non-invasive method to monitor fracture healing. These results suggest that NIRS could supplement radiographs and clinical impressions in daily clinical practice and may enable earlier diagnosis of nonunion.